UPIN AND IPIN ANIMATION RAMADAN EPISODE CONTAINS ISLAMIC VALUES FOR GRADE 1 STUDENTS OF MADRASAH IBTIDAIYYAH AL-HUDA I - Rohaeni, Neni; Suryani, Dewi; Wahyudi, Ira (PIONIR: JURNAL PENDIDIKAN, 2024)
Every child experiences a golden age in their development stage so they can easily learn from the environment around them. This momentum is very appropriate to incorporate the values of Islamic religious education into children's identity using various types of media, including film media. A film is a series of moving images that can attract everyone's attention. This research focuses on the Islamic values contained in the Upin and Ipin cartoon film Ramadan episodes for grade 1 students at MI Al-Huda I and what are the benefits for grade 1 students at MI Al-Huda I. This research aims to find out the values of Islamic education contained in the cartoon film Upin and Ipin in the Ramadhan episode, as well as the instillation of Islamic educational values in the cartoon film Upin and Ipin in the Ramadhan episode for class 1 at MI Al-Huda I. This research uses a qualitative descriptive approach and data collection through interviews and observations. The results and discussion of this research show that there are 2 worship services in the animated film Upin and Ipin Ramadhan episodes, namely mahdah worship such as prayer, fasting, paying zakat. Meanwhile, ghiru mahdah worship includes respecting elders, spreading kindness, helping each other, praying, and being patient.Keywords: Islamic Education Values, Upin and Ipin Films, Ramadhan Episodes, Internalization of Islamic Values